An apostle in battle: Paul and spiritual warfare in 2 Corinthians 12:1-10 - Bowens, Lisa M. (Wissenschaftliche Untersuchungen zum Neuen Testament / 2, 2017)
Chapter 1: Introduction -- 1.1 Proem -- 1.2 Snapshot of 2 Corinthians 12:1 and its context -- 1.3 Paul's Himmelsreise in recent interpretations -- 1.4 An epigrammatic survey of early Christian interpreters -- 1.5 Argument of the study -- 1.6 summary -- Chapter 2: Paul's cultural encyclopedia: Martial language and the cosmological, epistemological, and anthropological nexus -- 2.1 Introduction -- 2.2 Prelude to war: the apostle's appeal to the meekness and the gentleness of Christ (10:1-2) -- 2.3 the significance of the military imagery -- 2.4 Arena of warfare: The mind and knowledge of god 10:4-6 -- 2.5 The war scroll -- 2.6 1QS Treatise of the Two Spirits 3.13-4.26 -- 2.7 Excursus: an additional word on the War Scroll, the Treatise of the Two Spirits, and Paul -- 2.8 1QHa and the Aramaic Levi document -- 2.9 Summary and concluding thoughts -- Chapter 3: 2 Corinthians 12:1-10: an in-depth assessment -- 3.1 Introduction -- 3.2 Interpreting the passage-Corinthians 12:1-10 -- 3.3 Paul's heavenly journey: Real, literary, or both? -- 3.4 Bringing it all together: Paul's ascent, the War Scroll, the Treatise of the Two Spirits, 1QHa, and prayers of delivery -- 3.5 Excursus: Mithras liturgy -- 3.6 Snapshots of chapter 13:13:1-4, 13 -- 3.7 Paul's presents his life as an example -- 3.8 summary and concluding thoughts